(untitled) (Research, Society and Development, 2020)
Know the genetic variability between wheat cultivars (Triticum aestivum) is of great importance for breeding programs. Thus, this work aimed to use ISSR markers to access genetic diversity between contrasting wheat accessions. For this, 32 accessions of wheat and one access of triticale from the Active Bank of Wheat Germplasm of the Institute of Rural Development of Paraná (IDR-Paraná) were evaluated. A total of 66 polymorphic loci were amplified from 10 ISSR primers with an average loci variation per primer of 6.6. Genetic similarity ranged from 0.29 to 0.93, with an average of 0.57. The resulting dendrogram from the data was divided into four groups, in which it was observed that the genotypes LD 111202 and LD 111203 showed a high level of genetic similarity among themselves. The Bayesian cluster analysis formed four groups, partially in agreement with the UPGMA hierarchical cluster. ISSR markers were able to discriminate morphologically distinct and similar accessions and provide consistent information on the genetic variability between wheat genotypes that will help in breeding programs.